Kardiochirurgia DorosłychCałkowicie torakoskopowa chirurgiczna ablacja izolowanego migotania przedsionków metodą mikrofalową – pierwsze polskie doświadczenia - Hrapkowicz, Tomasz; Bisleri, Gianluigi; Kubacki, Krzysztof; Zembala, Michał; Foremny, Jerzy; Przybylski, Roman; Sokal, Adam; Nadziakiewicz, Paweł; Kalarus, Zbigniew; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Atrial fibrillation (AF) is a life-threatening arrhythmia that carries a high risk of thromboembolic complications. Moreover it is the most commonly occurring heart rhythm disorder. Surgical treatment of AF has become technically simpler and safer, and with recent advances in minimally invasive cardiac surgery, less traumatic. Following article describes the initial report on use of the minimally invasive, totally endoscopic, surgical treatment of lone AF. Aim: Safety and feasibility of minimally invasive, totally endoscopic, surgical treatment of lone AF was the primary aim of the study. Early results, evaluated as freedom from AF, were used as a secondary aim of the study Material and methods: 9 patients (pts) were included in the study (F=3; M=6, age range 37-64) with paroxysmal (n=4) persistent (n=3) and permanent (n=2) AF. Mean duration of AF was 58,8±29,3 months. Endoscopic instruments were introduced into the left pleural space via ports positioned as depicted on Fig. 1. Pericardium was opened longitudinally, 2 cm above the left phrenic nerve (Fig. 2) Transverse and oblique sinuses were then accessed, and Flex 10 Antenna (Guidant, Afix, Fremont, CA) was used to create a “box-like” lesion around pulmonary veins (Fig. 6) A microwave energy was used to create non-conducting lesions with standardized settings (60 Watts, 90 seconds). Pericardium was subsequently closed with single monofilament stiches, and pleural suction was applied. Results: There were no complications during or following the procedure. However, one female patient had to had sternotomy, due to technical difficulties in positioning Flex 10 antenna. On discharge 7 pts had the sinus rhythm, however in 3 of them electrical cardioversion had to be performed prior to discharge One patient experienced 3rd degree AV block, and was equipped with a pacemaker. However AV block resolved 5 days later, alleviating the need for constant AV stimulation. Four pts experienced brief episodes of AF, which resolved shortly after pharmacologic treatment. Moreover 1 pt had an episode of atrial flutter. Mean hospital stay was 4.7 days. Long term follow-up (56-392±217) indicates that 7 (77.7%) pts remain on sinus rhythm. Despite of the growing success of the percutaneous treatment of AF, surgical ablations offer the most precise and effective solutions. However, surgical options for lone AF were severely limited by the extend of sternal approach. Totally endoscopic, minimally invasive, surgical treatment of AF is safe and feasible, and offers promising early and mid-term results. Yet, long-term results need to be sought.